Pemanfaatan waktu luang asrama putra untuk mengaji di pondok pesantren darul kamal - Jayadi, Iqbal (LP2M STAI Darul Kamal NW Kembang Kerang NTB, 2022)
It is not surprising that the Arab community adorns the speed of time with the flash of a sword, al-waqt Ka al-saif fa in lam taqtha